Clock-Controlled and Cold-Induced CYCLING DOF FACTOR6 Alters Growth and Development in Arabidopsis - Blair, Emily J.; Goralogia, Greg S.; Lincoln, Matthew J.; Imaizumi, Takato; Nagel, Dawn H. (Frontiers in Plant Science, 2022)
The circadian clock represents a critical regulatory network, which allows plants to anticipate environmental changes as inputs and promote plant survival by regulating various physiological outputs. Here, we examine the function of the clock-regulated transcription factor, CYCLING DOF FACTOR 6 (CDF6), during cold stress in Arabidopsis thaliana. We found that the clock gates CDF6 transcript accumulation in the vasculature during cold stress. CDF6 mis-expression results in an altered flowering phenotype during both ambient and cold stress. A genome-wide transcriptome analysis links CDF6 to genes associated with flowering and seed germination during cold and ambient temperatures, respectively. Analysis of key floral regulators indicates that CDF6 alters flowering during cold stress by repressing photoperiodic flowering components, FLOWERING LOCUS T (FT), CONSTANS (CO), and BROTHER OF FT (BFT). Gene ontology enrichment further suggests that CDF6 regulates circadian and developmental associated genes. These results provide insights into how the clock-controlled CDF6 modulates plant development during moderate cold stress.